On the question of economic growth necessity: Evaluation of efficient rates and maintance of stable dynamics - Boris Kabylinskii; Andrey Dmitriev (Journal of Contemporary Economic and Business Issues, 2018)
This article analyzes the causes of economic growth. The authors revise social influences on the maintenance of economic expansion rates as a cause and effect together with maintaining the balance between aggregate demand and supply. They also give the main factors which give an impulse to a breach, as well as to a recovery of dynamic balance, including overseas trade factors. The main objective of the paper is to explore the possibilities of changing the approach to a consideration of a problem and define what a pressing need for economic growth is. The authors find out that profit should be considered as the 'negative' factor of economic growth, i.e. the growth serves as feedback on the response of the total profit increasing, or as a method of negotiation of its destabilizing influence. Another main idea of the paper is that continuous development of labor productivity (achievable through scientific and technical progress, business activity) together with a balanced policy on money supply is an inviolable factor for a sustainable economic growth. In conclusion, the authors suggest that the expansion of products export facilitates the stabilization of a country's economic situation and decreases the dependency on domestic demand, which is not always sufficient to cover the supply in a long-run equilibrium. At the same time, the possibilities for export expansion are limited, and one of the most significant constraints is determined by competitive and differently directed interests of countries entered in international trade flows as participations of a 'zero-sum play'.
Keywords: A11; B17; B40; 330; economic growth; consumption; savings; investment; external trade balance; aggregate profit; financial reserves